2020
DOI: 10.3390/jcm9103316
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gene Expression Associated with Collagen Regeneration and Remodeling of Extracellular Matrix after Percutaneous Electrolysis on Collagenase-Induced Achilles Tendinopathy in an Experimental Animal Model: A Pilot Study

Abstract: Percutaneous electrolysis is an emerging intervention proposed for the management of tendinopathies. Tendon pathology is characterized by a significant cell response to injury and gene expression. No study investigating changes in expression of those genes associated with collagen regeneration and remodeling of extracellular matrix has been conducted. The aim of this pilot study was to investigate gene expression changes after the application of percutaneous electrolysis on experimentally induced Achilles tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Percutaneous Needle Electrolysis (PNE) is a novel, minimally invasive approach involving the application of a galvanic electric current through a needle 1 . This procedure generates different alkaline molecules, capable of generating a non-thermal electrochemical ablation by cathodic flow directly into the affected tissue 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous Needle Electrolysis (PNE) is a novel, minimally invasive approach involving the application of a galvanic electric current through a needle 1 . This procedure generates different alkaline molecules, capable of generating a non-thermal electrochemical ablation by cathodic flow directly into the affected tissue 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering US as the first-line imaging modality to diagnosis and follow-up of musculoskeletal injuries [10], it was not necessary to perform magnetic resonance imaging like other studies [27]. Nowadays, in the field of sports, there is an urgent need to improve the interpretation of ultrasound images to establish accuracy diagnoses and apply the best treatment options, from a regenerative therapeutic point of view [28,29]. Hence, there is a huge enthusiasm in knowing soleus muscle features and having a better knowledge of pathological characteristics [6,7,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Although these hypotheses have been proposed based on clinical results, and mechanistic research contrasting them is scarce, pioneering works have examined the histologic and molecular response produced by the PE application to tendon or muscle in rats. These authors have reported an increase in the expression of anti-inflammatory proteins, angiogenic factors, and some genes related to collagen regeneration and a decrease in pro-inflammatory mediators [ 5 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%